Ultrastructural evaluation of enamel surface morphology after tooth bleaching followed by the application of protective pastes. Issue 3 (16th September 2015) - Poggio, Claudio; Grasso, Nicolò; Ceci, Matteo; Beltrami, Riccardo; Colombo, Marco; Chiesa, Marco
Summary: The aim of the present in vitro study was to evaluate the morphology of bleached enamel surface followed by the application of different protective pastes. Specimens were prepared from 50 human incisors free of caries and defects. The bleaching procedure was performed with 35% hydrogen peroxide (Perfect Bleach Office+). For the remineralization treatment, different protective pastes (Tooth Mousse, MI Paste Plus, Remin Pro, and Profluorid Varnish) were evaluated. Specimens were randomly assigned to 10 groups of 5 specimens each. The specimens were analyzed under scanning electron microscopy. The superficial morphology of enamel was examined and scored as follows: 0, enamel with smooth surface morphology; 1, enamel with slight irregularities; 2, enamel with moderate irregularities; 3, enamel with accentuated irregularities. The photomicrographs were evaluated in a double‐blind manner by three examiners, previously calibrated. Results were analyzed by a Kruskal–Wallis nonparametric test, at the significance level of 0.05. Dunn method posttest was applied for multiple comparisons. A different superficial morphology was observed among control group specimens and specimens treated with bleaching agent and protective pastes (p < 0.05). Enamel bleached showed pronounced surface changes and irregularities, significantly different from other groups except for groups 8 (enamel + Perfect Bleach Office+ + Remin Pro) and 10 (enamel + Perfect Bleach Office+ + Profluorid Varnish) (p > 0.05). The application of the tested pastes after bleaching is effective on repairing enamel surface morphology, demonstrating a higher efficacy for the CPP‐ACP products compared to fluoridated ones. SCANNING 38:221–226, 2016. © 2015 Wiley Periodicals, Inc.